Differences between take-off behavior during vertical jumps and two artistic elements - Droszez, A.; Sanno, M.; Goldmann, J.-P.; Albracht, K.; Brüggemann, G. P.; Braunstein, B. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
The present study analysed the possible application of vertical jumps as a diagnostic tool for the acrobatic elements backward somersault (6s) and Menichelli (MEN). Therefore, 14 female gymnasts of the German national squad performed dassical vertical jumps (CMJ, SJ, DJ), backward somersaults and Menichellis during a diagnostic camp at the German Research Centre of Elite Sport (momentum). Kinematic and kinetic parameters were captured by a 30-motion capture system and two force plates. Take off velocities of the CMJ and backward somersault showed significant correlations (r=0.86). Besides possible predictions for take4ff velocity of BS performing CMJ, findings did not address execution of MEN. Concerning training purposes, vertical jumping does not affect performance characteristics of acrobatic elements.